Geocentric Finance Equity to Improve Financial Institution Performance - Sukendri, Nengah (LPPM Universitas Ekasakti, 2024)
This study aims to bridge the research gap as a solution to improve the performance of financial institutions by using a qualitative research approach by analysing and synthesising established literature and theories. The researcher determined a theme that links equity with financial institutions by examining equity materials, geography and the performance of financial institutions with a locus in West Nusa Tenggara Province. This research succeeded in finding a new concept that is expected to be a bridge to overcome the research gap. The new concept with the name Geocentric Finance Equity is expected to improve the performance of financial institutions The government and the private sector have developed BPRs in each Regency and City with the aim of providing banking services. The government and the private sector have developed BPRs in each Regency and City with the aim of providing banking services.